Ultrasound detection of twinning in Equus asinus- A case report - TANDON, S N; VYAS, SUMANT; LEGHA, R A (The Indian Journal of Animal Reproduction, 2007)
A rare case report of twinning in Equus asinus Genny) detected by ultrasound is being reported.